Clown Curalina (Drica Santos) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
Photographic work by the actress, clown, producer, researcher and collaborating professor at the Department of Performing Arts at CEART/UDESC. Doctor and Master in Theater by PPGT/UDESC. Graduated from the Bachelor's Degree in Artistic Education (Hab. Performing Arts) at UDESC.
Keywords: Clown; Photographic work; Actress